Ukrainian national identity and legal culture - Trubchaninov, K. S. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The introduction of legislative regulation in the sphere of strengthening Ukrainian national and civic identity determines the topicality of scholarly research into the political, state and legal aspects of Ukrainian national identity. Thus, to fulfill one of the main tasks of Ukraine’s state policy in this area of eliminating the influence of the aggressor state in informational, educational, and cultural spheres of Ukraine, it is necessary to investigate the influence of Russian legal culture on the formation of contemporary Ukrainian national identity, which is grounded on the European values such as rule of law and respect for human dignity and human rights and freedoms. The results of the research demonstrate that the historical experience of over three-hundred years of Ukrainian ethnic territories being governed by the Tsardom of Moscow, the Russian Empire and the Soviet Union have had negative effects on development of Ukrainian national legal culture. Especially legal nihilism has been crystallized in Ukrainian legal mentality, which is still manifested in the content of higher legal education and legal training of public officials (e. g., military servicemen of the Armed Forces of Ukraine, National Guard of Ukraine, State Border Guard Service of Ukraine, Security Service of Ukraine etc.), and legal practice. It is concluded that preserving state independence, restoring state sovereignty and territorial integrity of Ukraine within internationally recognized borders requires eliminating the influence of the legal culture of Russian statehood in various forms on the national legal system of Ukraine. To this end, it is suggested to implement measures to increase the overall level of legal culture of contemporary Ukrainian society (e. g., identify the remnants of Russian genesis in societal legal consciousness, professional legal consciousness of lawyers and competent legal consciousness of public officials and replace them by means of legal education with European values, which lay in foundations of Ukraine’s legal order, improve efficiency of human rights’ protection).